THE EFFECT OF SUBSTITUTION OF FISH MEAL WITH FRESH BLACK SOLDIER FLY LARVAE IN FEED FORMULATION ON THE GROWTH OF TILAPIA (Oreochromis sp.) - Helmiati, Senny; Fathina, Hamda Raihana (Jurnal Perikanan Unram, 2025)
The high price of feed is caused by the high price of fish meal as a raw material for protein-source of feed. Black Soldier Fly (BSF) larvae have good nutrient content, so they can be used as an alternative raw material for feed. This research aims to determine the effect of fish meal substitution with fresh BSF larvae on the growth performance of tilapia (Oreochromis sp.). The research was designed using a completely randomized design with four treatments in the form of fishmeal substitution with BSF larvae and triplicates, including P1 (0%), P2 (25%), P3 (50%), and P4 (75%). The average weight of individual fish used was 17,98±1,49 g with a stocking density of 20 fish tank-1 and kept for 60 days in fiber tanks measuring 50x50x60 cm3. Feed is given as much as 3% of the fish biomass with a frequency of giving twice per day at 08.00 am and 15.00 pm. The data were analyzed using analysis of variance with a significance level of 95%. If there is a significant difference, further testing is carried out using Duncan's Multiple Range Test. Water quality data were analyzed descriptively. The research results proved that fresh BSF larvae could replace fish meal by 75% (P<0,05). Substitution of fish meal with fresh BSF larvae as much as 75% resulted in absolute growth rate based on length of 6,16±0,38 cm, absolute growth based on weight of 53,41±10,40 g, specific growth rate based on length of 0,10±0,01 % day-1, weight-based specific growth rate of 0,89±0,17% day-1, feed conversion ratio of 1,13±0,14 and feed efficiency of 89,71±10,81%.